PENGARUH WORKLOAD TERHADAP KINERJA DENGAN DIMEDIASI STRES KARYAWAN OJK REGIONAL BENGKULU - Aandriyani Prawitasari; Meiffa Herfianti (Creative Research Management Journal, 2020)
This study aims to determine the effect of workload and stress on employees performance ofBengkulu Regional Otoritas Jasa Keuangan Employees. The type of research used in thisresearch is quantitative. The sample is 42 people, which is the entire population. Datacollection methods used were questionnaires. Data were analyzed by path analysis model withSmart PLS 2.0 program to determine the relationship between variables. The result showed allhypotesis was accepted. The results showed that partially the workload and stress has anegative and significant effect on performance, workload has a positive and significant effect onstress. For indirect influence, influential workload positive and significant impact on employeeperformance through work stress of Bengkulu Regional Otoritas Jasa Keuangan.